A case report of COVID-19-associated acute hand ischaemia in a young professional volleyball player. Issue 3 (23rd February 2022) - Achim, Alexandru; Kákonyi, Kornél; Jambrik, Zoltán; Ruzsa, Zoltán
Abstract: Background: Several coronavirus disease-19 (COVID-19)-associated complications are being increasingly reported, including arterial and venous thrombo-embolic events that may lead to amputation of the affected limbs. So far, acute upper limb ischaemia (ULI) has been reported only in critically ill patients. Case summary: Herein, we aimed to present a case of a 29-year-old, otherwise healthy male volleyball player, with acute ischaemic signs in the upper extremity who was diagnosed with COVID-19 1 month before the ischaemic event. It has been shown that volleyball players experience repetitive stress that involves their hands and, in particular, their fingers. Repetitive trauma can lead to local vascular abnormalities, such as reduced capillarization and lower resting blood flow that can lead to pain and cold digits, but never acute ULI. Discussion: To our knowledge, this is the first case of such a hypercoagulable synergistic mechanism that leads to a high thrombus burden. Intra-arterial local thrombolysis and percutaneous transluminal angioplasty failed to succeed, and percutaneous large-bore embolectomy with the Indigo Aspiration System (Penumbra Inc., CA, USA) was deemed necessary.